2019
DOI: 10.3389/fphar.2019.01371
|View full text |Cite
|
Sign up to set email alerts
|

XIAOPI Formula Inhibits Breast Cancer Stem Cells via Suppressing Tumor-Associated Macrophages/C-X-C Motif Chemokine Ligand 1 Pathway

Abstract: Macrophages are the most abundant stromal cells associated with the host immune system in multiple malignancies including breast cancer. With proven clinical efficacy and no noticeable adverse effects, XIAOPI formula (XPS) has been approved for breast hyperplasia treatment by the State Food and Drug Administration of China (SFDA) in 2018. The existing knowledge about the anti-breast cancer activities and mechanisms of XPS has been very limited. The present study aimed to investigate whether XPS could exert an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…Our previous studies have found that CXCL1 is one of the most abundant chemokines secreted by TAMs [ 16 , 17 ]. TAM/CXCL1 inhibition represents a promising treatment strategy for preventing breast cancer immune escape and lung metastasis [ 17 , 18 ]. For example, CXCL1 derived from TAMs could recruit hematopoietic stem and progenitor cells (HSPCs) and induce their differentiation into MDSCs to shape the immunosuppressive TME and favor breast cancer metastasis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have found that CXCL1 is one of the most abundant chemokines secreted by TAMs [ 16 , 17 ]. TAM/CXCL1 inhibition represents a promising treatment strategy for preventing breast cancer immune escape and lung metastasis [ 17 , 18 ]. For example, CXCL1 derived from TAMs could recruit hematopoietic stem and progenitor cells (HSPCs) and induce their differentiation into MDSCs to shape the immunosuppressive TME and favor breast cancer metastasis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, GM-CSF and IL-6 could not only promote the myeloid-biased differentiation, but also induce the differentiation of myeloid precursors into functional MDSCs [40]. However, our previous findings demonstrated that CXCL1 acts as the highest chemokine secreted by TAMs isolated from breast cancer [16,41]. Moreover, CXCL1 silencing in TAMs was found to inhibit breast cancer growth and lung metastasis via inhibiting NF-κB/SOX4 signaling in both murine and human models [42].…”
Section: Discussionmentioning
confidence: 93%
“…However, our study demonstrated that XIAOPI formula could inhibit CXCL1 mRNA and protein expression. More importantly, our previous studies indicated that XIAOPI formula suppressed the promoter activity of CXCL1 gene in TAMs [41]. Meanwhile, XIAOPI formula contains thousands of phytochemicals and molecular targets, which shows a natural advantage than CXCL1 mono-targeting strategy.…”
Section: Discussionmentioning
confidence: 97%
“…C-X-C motif chemokine ligand 1 (CXCL1) is a chemokine secreted by macrophages whose expression in the tumor stroma is associated with poor prognosis and BC metastasis [ 55 , 56 ]. Interestingly, pharmacological inhibition of TAM-derived CXCL1 suppresses BCSCs [ 57 ]. Two complementary studies indicate that other cytokines such as interleukin-1beta (IL-1β) may be involved in the cross-talk between macrophages and BCSCs.…”
Section: The Tumor Microenvironment and The Breast Cancer Stem Celmentioning
confidence: 99%